Generalized Hermite–Hadamard-Type Integral Inequalities for h-Godunova–Levin Functions. (14th March 2022) - Ali, Rana Safdar; Mubeen, Shahid; Ali, Sabila; Rahman, Gauhar; Younis, Jihad; Ali, Asad
Abstract : The main objective of this article is to establish generalized fractional Hermite–Hadamard and related type integral inequalities for h -Godunova–Levin convexity and h -Godunova–Levin preinvexity with extended Wright generalized Bessel function acting as kernel. Moreover, Hermite–Hadamard-type and trapezoid-type inequalities for several known convexities including Godunova–Levin function, classical convex, s -Godunova–Levin function, P -function, and s -convex function are deduced as corollaries. These obtained results are analyzed in the form of generalization of fractional inequalities.